Explaining the Role of National Participant Geospatial Information System in the Effectiveness of Urban Services with a New Approach - Mahdi Fallah; Tajaddin Karami; Mousa Kamanroudi (JURNAL GEOGRAFI, 2023)
This article is written with a new approach of an integrated system, under the title of National Participatory Geographical Information System, which is introduced. This approach originated from people's thoughts in dealing with national and transnational issues and issues in the form of participation, which has challenged human evaluations and needs to educate everyone. Now, researchers, stakeholders, and government officials' primary concern are finding ways to increase public participation in these programs. Especially digital cities have been made available in line with all the angles of virtual planning. In the coming years, how to deal with technology in the framework of a coordinated information system dependent on space-time-place is very important. After platform creation, it must be managed and can be used and developed within the requirements management framework. A case study was chosen to prove the applicability of this study. The problem of the wrong cycle is a general process with the aim of its educational structural correctionKeywords: New Geography, Education NPGIS, Virtual Cities, Next Generation